Frequency component mixing of pulsed or multi-frequency eddy current testing for nonferromagnetic plate thickness measurement using a multi-gene genetic programming algorithm - Ge, Jiuhao; Yusa, Noritaka; Fan, Mengbao (NDT & E international : independent nondestructive testing and evaluation, 2021)
For the efficient use of frequency components, a frequency mixed feature for pulsed eddy current testing (PECT) or multi-frequency eddy current testing (MultiECT) was proposed for nonferromagnetic plate thickness measurement. An evolutionary algorithm multigene genetic programming was employed to mix the frequency components using the best linearity as a target. Time domain and frequency domain finite element simulations of PECT and MultiECT were conducted. The simulation results revealed that, in terms of thickness measurement, a mixed feature comprising two or three frequencies was more linear and accurate than the traditional peak time and decay coefficient of PECT. Experiments were conducted to validate the results of the simulations and to test the mixed feature in aluminum plate thickness evaluations. The experimental results also revealed that the use of more frequencies did not always increase the accuracy of thickness evaluations. Proper frequency component selection was more efficient than blindly increasing frequency numbers. •Gini coefficient is used to indicate linearity between feature and thickness.•The mixed feature comprising two or three frequencies is better than the peak time and decay coefficient of PECT.•The use of more frequencies does not always increase the accuracy of thickness evaluations.